Analisis Strategi Optimalisasi Portofolio Saham LQ 45 (pada Bursa Efek Indonesia Tahun 2009-2011) (Jurnal Manajemen dan Organisasi, 2016)
Capital market is a meeting place for people who have excess money and those who need money for  transaction of security. Every investor needs optimal profits with minimal risk. Portfolio is basically related to how one allocates a number of stocks into various investment types that results in optimal profits. By making diversification, investors may reduce the rate of risk and at the sametime optimize the rate of expected return. Based on this case this research raises the problem of how to design an optimal portfolio simulation. i.e. a combination of liquid shares LQ 45 list ini Indonesian Stock Exchange in the period of 2009-2011 by using two methods, using Single Index Model and Indexing. Single index Model is a model of portfolio analysis using the account of Excess Return to Beta (ERB) ratio and value of C* to gain optimal shares  on portfolio. The procedure of indexing is to make one’s own group i.e liquid LQ 45 calculating the risk and return then compare the result with Single Index Model, the procedure of all securities are ranked by ERB instead of Excess Return to Risk (ERR). After securities were ranked using the above ratio, securities with greater Excess return to standart deviation and cut off point (C*) were included into the optimal portfolio. The conclusion of this research is that it is better to choose Single Index Model as the methode  resulting in optimal profits.  Keyword: Optimum portfolio, LQ 45, single index, indexing